Assessment of the severity of anxiety, depression, substance use, and resilience of children and youths aged 10–24 years in the South West Region of Cameroon - Lifafa Kinge Kange; Eyong Clovert; Ayuketang Eyong Ashu; Tangi Regobell Mua; Ashley Wotany Luma; Ghangha Jamin Ghangha; Ruth Amin; Wirnkar Jude Kanla; Asanga Ngu Winston; Vamtowe Hezal Tracy; et al. (Eximia, 2024)
Background: Many youths in Cameroon and in the South West region of the country face socio-economic hardships that have affected their mental health and resilience. This study aimed at delving into these critical areas and explore the interplay between anxiety, depression, substance use, and resilience in the children and youth of the South West Region, Cameroon. Materials and method: This study was a cross-sectional study conducted for a period of 14 months. Consecutive sampling was used to select the participants wherein peer educators with lived experience administered structured questionnaires to youths in other to assess the severity of anxiety, depression, substance use, and resilience using standardized WHO scales. Data obtained from the participants were coded, entered into a data collection form designed with Kobo collect tool then into Microsoft Excel 2016 and analyzed using Statistical Package for the Social Sciences, version 25. Results: A total of 1,173 participants were recruited with an average age of 18.32 years. The overall prevalence of mental disorders was 73.1%. The results showed that 74 (6.3%) had severe anxiety, 207 (17.6%) had moderate anxiety, and the and majority 518 (44.2%) were normal. For suicide screening, 79.5% were normal, while 20.5% had suicidal thoughts. When screened for depression, 19 (1.6%) had severe depression and the majority of participants had minimal depression with a with a percentage of 831 (70.8%). The overall level of low resilience was 91.0% (1,068). Logistic regression analysis showed that age group and location had significant associations (P-value <0.05) with the level of resilience. Pearson’s correlation analysis revealed a significant but weak correlation between anxiety, resilience, depression status and substance status and substance use with correlation coefficients of 0.245, 0.079 and 0.254 respectively. Conclusion: Anxiety, depression and substance use disorders are predominantly the mental health problems amongst youths 10 – 24 years in the Southwest Region of Cameroon. Severe anxiety in youth is linked to an increased risk of developing other mental health issues, such as depression and substance use disorders. The consequence of depression amongst youths if left unattended to can lead to increased likelihood of persistent mental health problems in adulthood.